Global Distribution and Future Projections of Functional Groups Within Extremotolerant Soil Fungi - Claudia Coleine; Federico Biagioli; Tadeo Sáez‐Sandino; Leho Tedersoo; Claudio Donati; Miriam Muñoz‐Rojas; Lucia Muggia; Manuel Delgado‐Baquerizo (Global Change Biology, 2026)
Black fungi are often described as ubiquitous specialists of harsh environments (extremotolerant), yet how their ecological lifestyles vary across environmental gradients remains poorly understood. Here, we use a global soil dataset based on ITS PacBio sequencing to characterize over 51,000 black fungal phylotypes across major functional groups and ascomycete lineages, including Chaetothyriales and Capnodiales. We find that their global distribution is strongly structured by lifestyles and environmental filtering, especially from climate. Capnodiales dominate arid regions, whereas Chaetothyriales are associated with cold and montane environments. Functional strategies further explain global patterns, with rock‐inhabiting fungi exhibiting the broadest niche breadth and highest environmental tolerance. We also revealed limited niche conservatism and widespread convergence in stress‐tolerance traits, suggesting repeated evolutionary adaptation to extreme conditions. Climate projections further suggest a spatial reorganization of dominant taxa and functional groups under future scenarios, with stress‐tolerant fungi tracking the expansion of arid environments while plant pathogens are predicted to persist in current core regions and expand into areas where they are presently marginal. These findings challenge simplified representations of extremotolerant fungi in Earth system models and indicate current approaches may misrepresent how soil microbial communities reorganize under climate change.